2014
DOI: 10.1177/1078155214527145
|View full text |Cite
|
Sign up to set email alerts
|

Does gastric acid suppression affect sunitinib efficacy in patients with advanced or metastatic renal cell cancer?

Abstract: There was a significant difference in progression-free survival and overall survival between the acid suppressed and no acid suppression groups. Further research is required to confirm this potential interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…Ha et al showed that in 231 patients with renal clear cell carcinoma the association of Sunitinib and PPIs was related with shorter progression-free and overall survival (Ha et al, 2015). Similarly, in a series of 507 lung cancer patients undergoing treatment with Erlotinib, the concomitant administration of PPIs was related with shorter progression-free and overall survival .…”
Section: Interaction Of Ppi With Oral Anticancer Agentsmentioning
confidence: 99%
“…Ha et al showed that in 231 patients with renal clear cell carcinoma the association of Sunitinib and PPIs was related with shorter progression-free and overall survival (Ha et al, 2015). Similarly, in a series of 507 lung cancer patients undergoing treatment with Erlotinib, the concomitant administration of PPIs was related with shorter progression-free and overall survival .…”
Section: Interaction Of Ppi With Oral Anticancer Agentsmentioning
confidence: 99%
“…Most importantly, acid-inhibitory drugs, such as proton pump inhibitors (PPIs), increase the intragastric pH, which may decrease the solubility and thereby the biological availability of certain TKIs. Although there are no prospective studies available, some retrospective data clearly showed that PPI use was associated with decreased TKI efficacy [57]. …”
Section: Introductionmentioning
confidence: 99%
“…128 Gastrointestinal adverse effects of sunitinib may potentiate the use of proton pump inhibitors. 126 However, acidsuppressing agents are suspected to decrease absorption and hence its efficacy. 126,142 Food does not significantly influence sunitinib's bioavailability.…”
Section: Pharmacogenetic And/or Drug-induced Changes In Metabolizing mentioning
confidence: 99%
“…126 However, acidsuppressing agents are suspected to decrease absorption and hence its efficacy. 126,142 Food does not significantly influence sunitinib's bioavailability. 154 The effect of acid-reducing agents on the absorption of both vandetanib and venurafenib has not been studied, but based on solubility data is anticipated to be insignificant.…”
Section: Pharmacogenetic And/or Drug-induced Changes In Metabolizing mentioning
confidence: 99%
See 1 more Smart Citation